2018
DOI: 10.7759/cureus.2258
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Lavage of Extensive Chronic Subdural Hematoma in an Infant After Abusive Head Trauma: Adaptation of a Technique From Ventricular Neuroendoscopy

Abstract: Subdural fluid collections are frequently encountered in young children after non-accidental injury. In a subset of patients, these collections progress in size and ultimately require permanent drainage, which is commonly achieved with subdural-peritoneal shunts. However, excessive protein and cellular contents in the fluid are potential risk factors for shunt failure. Here, we describe the adaptation of an endoscopic lavage technique established for ventricular endoscopy with the aim of improving fluid condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Endoscopic lavage before shunting can remove protein and cellular debris to improve the success rate of shunt surgery. 4 Although there was no infant in our series, endoscopic evacuation of subdural hematomas was also found to be effective in infants. 18 Although we did not come across any recurrence in our series, it could be due to the small number of cases with a short follow-up.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Endoscopic lavage before shunting can remove protein and cellular debris to improve the success rate of shunt surgery. 4 Although there was no infant in our series, endoscopic evacuation of subdural hematomas was also found to be effective in infants. 18 Although we did not come across any recurrence in our series, it could be due to the small number of cases with a short follow-up.…”
Section: Discussionmentioning
confidence: 65%
“…It provides good visualization compared with the flexible scope. There are reports of use of both rigid [1][2][3][4]8,10,[12][13][14]17,19,21 and flexible scopes 5,9,11 in the management of CSDH. There may be difficulty in advancing the rigid scope, especially when the bony opening is not selected properly.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we selected neuroendoscopy because of the massive collection of fluid in the subdural space. In addition, few studies have reported its use in drainage of chronic subdural hematomas [ 2 - 5 , 8 ]. To our knowledge, this is the second report of the use of neuroendoscopy to approach massive bilateral chronic subdural hematomas in children [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, few studies have reported its use in drainage of chronic subdural hematomas [ 2 - 5 , 8 ]. To our knowledge, this is the second report of the use of neuroendoscopy to approach massive bilateral chronic subdural hematomas in children [ 2 ]. However, despite the presence of a bilateral chronic hematoma, non-accidental head trauma was ruled out after deep investigation to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation